3(4x+3)-5=6(2x-2)

Simple and best practice solution for 3(4x+3)-5=6(2x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(4x+3)-5=6(2x-2) equation:



3(4x+3)-5=6(2x-2)
We move all terms to the left:
3(4x+3)-5-(6(2x-2))=0
We multiply parentheses
12x-(6(2x-2))+9-5=0
We calculate terms in parentheses: -(6(2x-2)), so:
6(2x-2)
We multiply parentheses
12x-12
Back to the equation:
-(12x-12)
We add all the numbers together, and all the variables
12x-(12x-12)+4=0
We get rid of parentheses
12x-12x+12+4=0
We add all the numbers together, and all the variables
16!=0
There is no solution for this equation

See similar equations:

| 6d-6=¾(4d+8) | | 2y-(3-y)/4=15/4 | | x+44=3x-10 | | 7a-4=a=5 | | 450+0.03s=21667 | | 8x-27=125 | | 35=32-1/3x | | −46+x=5 | | 12=3−q | | 2x+20=-2x-20 | | 96x×2=24x×2 | | -2=-5+m/9 | | p/35=2/28 | | 3.20+6x=18.20 | | -12=s/4+-9 | | -17=4-3z | | 1x+5=3×-2 | | 2(x+5)+3(x+8)=44 | | -6x=3.16 | | 84=-3(-4+3p) | | 2x–45=9x+10 | | 4.5k=5.1k-30 | | 7x+3x+10=-90 | | 5(1x+6)=-20 | | p35=228 | | 96x×2=24x | | 3x=72x+8 | | 12+2x+x=3x+3 | | -9x=10-4x | | 32+2/5=x | | (2x-26)=94 | | -9+x+2x+3=(3x+2) |

Equations solver categories